The first Pd-catalyzed Buchwald–Hartwig aminations at C-2 or C-4 in the estrone series - Ildikó Bacsa (Beilstein Journal of Organic Chemistry, 2018)
A facile Pd-catalyzed C(sp2)–N coupling to provide a range of 2- or 4-[(subst.)phenyl]amino-13α-estrone derivatives has been achieved under microwave irradiation. The reactions were mediated with the use of Pd(OAc)2 as a catalyst and KOt-Bu as a base in the presence of X-Phos as a ligand. The desired products have been obtained in good to excellent yields. The nature and the position of the aniline substituent at the aromatic ring influenced the outcome of the couplings. 2-Amino-13α-estrone was also synthesized in a two-step protocol including an amination of 2-bromo-13α-estrone 3-benzyl ether with benzophenone imine and subsequent hydrogenolysis.